Economic analysis of alternative logistics systems for Tennessee-produced switchgrass to penetrate energy markets. (February 2016) - Chugh, Shikha; Yu, T. Edward; Jackson, Samuel W.; Larson, James A.; English, Burton C.; Cho, Seong-Hoon
Abstract: Growing biomass crops for energy production on low productivity lands not used for food production has been suggested as an alternative to reduce dependence on fossil fuels and to mitigate greenhouse gas emissions from transportation fuel. Switchgrass is considered a potential feedstock in various states, including Tennessee, given its high biomass content in a wide range of environments. However, its low density relative to energy value and resulting high logistics costs impede the profitability of switchgrass-based bioenergy. The objective of this study is to determine the optimal logistics configuration for a collection/distribution hub to market Tennessee-produced switchgrass for bioenergy production. A mathematical programming model integrated with a geographic information system is used to maximize the net present value of profit from a hub that serves switchgrass producers and bioenergy markets. Six logistics configurations delivering switchgrass to local or international bioenergy markets are evaluated. The results highlight the economic challenges of penetrating energy markets for a switchgrass collection/distribution hub – only one logistics configuration that targets the local market is profitable. However, serving local and international markets becomes more feasible as investment risk declines. The results imply that a clear direction for national bioenergy policy is crucial to developing a biomass feedstock for the U.S. bioenergy industry. Highlights: We study the economics of supplying Tennessee-produced switchgrass for bioenergy. Six switchgrass logistics pathways proposed by a collection hub are evaluated. Only one logistics configuration that targets the local market is profitable. Serving international markets becomes more feasible as investment risk declines.